Lipid nanoparticle GM-CSF replacement for autoimmune pulmonary alveolar proteinosis - Liming Lian; Bora Jang; Sebastian G. Huayamares; Avraham Shakked; Kara Gentry; Ryan Zenhausern; Afsane Radmand; Elisa Schrader Echeverri; Vaunita C. Parihar; Ricardo C. Guerrero-Ferreira; Randi Calkins; Daryll Vanover; et al. (Proceedings of the National Academy of Sciences, 2026)
Granulocyte–macrophage colony-stimulating factor (GM-CSF) deficiency drives autoimmune pulmonary alveolar proteinosis (aPAP), a disease characterized by impaired macrophage-mediated clearance of pulmonary surfactants. Clinical data suggest that inhaled recombinant GM-CSF reduces symptoms in aPAP patients, providing a rationale for mRNA-based GM-CSF replacement therapies. However, these require effective mRNA delivery after nebulization. Here, we report the iterative in vivo design of a lipid nanoparticle, named nebulized lung delivery 2 (NLD2), that efficiently delivers mRNA after nebulization. NLD2 carrying GM-CSF mRNA transfected alveolar macrophages in vivo, leading to interleukin-10 pathway activation and subsequent surfactant lipoprotein clearance. In a preclinical disease model of aPAP, GM-CSF mRNA delivery reduced surfactant protein thickness more than recombinant GM-CSF. These data support continued exploration of nebulized lipid nanoparticle therapies for aPAP.